Designing an Used Goods Donation System to Reduce Waste Accumulation Using the WASPAS Method - Wayahdi, M. Rhifky; Ruziq, Fahmi (Politeknik Ganesha Medan, 2024)
This research aims to build a website application-based selection system for recipients of used goods donations using the WASPAS method. This system is designed to assist in the efficient and fair distribution of used goods to recipients in need. The WASPAS method is applied to calculate the preference value (Qi) for each alternative donation recipient based on predetermined criteria. The analysis results show that